Financial Risk and Performance of National Private Foreign Exchange Commercial Bank: Moderating Effects of Bank Size - Olivia, Chintya; Atahau, Apriani Dorkas Rambu; Martono, Samuel (Jurnal Keuangan dan Perbankan, 2022)
This study aims to analyze the effect of risk on financial performance and the moderating effect of bank size on the relationship between risk and financial performance. This study uses seven Foreign Exchange National Private Commercial Banks listed on the IDX 2015-2019 as the samples. The analytical method used is a panel data regression model with STATA 16.0 software. Empirical results show that liquidity and credit risk have no effect on financial performance. Market risk has a significant positive effect on financial performance while operational risk has a significant negative effect on financial performance. Bank size  moderate the effect of liquidity and credit risk on financial performance but failed to moderate the effect of market and operational risk on financial performance. These findings imply that national foreign exchange private commercial banks listed on the IDX for the 2015-2019 period should pay attention to the market and liquidity risks as those risks affect banks’ profitability, especially for large banks.